2004
DOI: 10.1093/jac/dkh388
|View full text |Cite
|
Sign up to set email alerts
|

Variability and variation in drug susceptibility among Giardia duodenalis isolates and clones exposed to 5-nitroimidazoles and benzimidazoles in vitro

Abstract: Our observations support the idea that G. duodenalis cultures exhibit variations in their response to 5-nitroimidazoles and benzimidazoles as a result of a drug-independent competition between drug-susceptible and drug-resistant subpopulations when parasites are subcultured.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 41 publications
0
33
0
1
Order By: Relevance
“…1) using subculture in liquid medium. Briefly, trophozoites (7.5 × 10 5 ) were incubated with the inhibitors for 30 min at 37 o C, washed twice with PBS and subcultured in fresh medium for 48 h at 37 o C. The cells were counted and their viability was determined by interpolation in a control curve obtained with different inocula of untreated trophozoites (Argüello-García et al 2004), and the experimental lethal concentrations at 50 and 20% (LC 50 and LC 20 respectively) were also calculated. The data obtained showed that E64 was a potent inhibitor with a LC 50 value of 7.47 µM.…”
mentioning
confidence: 99%
“…1) using subculture in liquid medium. Briefly, trophozoites (7.5 × 10 5 ) were incubated with the inhibitors for 30 min at 37 o C, washed twice with PBS and subcultured in fresh medium for 48 h at 37 o C. The cells were counted and their viability was determined by interpolation in a control curve obtained with different inocula of untreated trophozoites (Argüello-García et al 2004), and the experimental lethal concentrations at 50 and 20% (LC 50 and LC 20 respectively) were also calculated. The data obtained showed that E64 was a potent inhibitor with a LC 50 value of 7.47 µM.…”
mentioning
confidence: 99%
“…Three of these hit compounds, benzalkonium chloride, paroxetine hydrochloride, and oxibendazole, were previously shown to have antibacterial activity (37)(38)(39). These three known antimicrobial compounds, as well as two additional hits, ethidium bromide (because it is associated with broad toxicity) and acetaminophen (because it was a false hit that was not confirmed in secondary screens), were not investigated further.…”
Section: Resultsmentioning
confidence: 99%
“…Here, we also noted that trichomonad ATP readouts in this assay system are unreliable at concentrations below the MIC. Thus as previously commented (Argüello-García et al 2004;Upcroft and Upcroft 2001a), susceptibility assays and readouts can vary greatly within and between laboratories depending on the assay system. We also tested the parasite phosphatase activity assay described by MartinezGrueiro et al (2003), but the ID 90 readouts did not correlate with our MIC values for all drugs used (data not shown).…”
Section: Discussionmentioning
confidence: 98%